The Intensification of Russian- Turkish Relations: the Essence and the Prospect - Y. S. Kudryashova (Vestnik MGIMO-Universiteta)
Russian-Turkish relations are developing difficultly, mutual distrust still presents, many regional problems are not settled, at the same time Russia is not interested in Turkish expansion in Eurasia. Nevertheless successful economic cooperation inevitably provides a firm basis for political rapprochement and advancing development of mutual trust in our relations. Intensive Russian-Turkish business connection provided the situation of both countries’ interdependency in tradeeconomic and energetic spheres. This situation led to the formation of Russian-Turkish political partnership.